Development of research continuous usage intention of e-commerce. A systematic review of literature from 2009 to 2015 - Ali Harasis, Ahmad; Imran Qureshi, Muhamamd; Rasli, Amran (International Journal of Engineering and Technology, 2018)
This paper systematically reviews the literature on the continuous usage intentions from 2009 to 2015.Â From the review of literature on continuance usage intentions, some models have been put forward to explain the continuity of the e-Commerce. However, each model is extensively different from one another. Over the years, a considerable development in the literature of Continuous intentions. However, there is still a necessity to present a more comprehensive and integrative model for the continuance usage intention of e-commerce users than the models in existence at the moment. The Expectation Confirmation Model (ECM) has been widely accepted in general. In addition, many researchers stated that ECM model can be employed to look into e-commerce better than other existing models and theories.Â Â